Performance of Indian mustard as influenced by plant growth regulatorbrassinosteroid under the Western Arid Region of Rajasthan - Babloo Sharma; KG Vyas; Sunil Kumar Sharma; Reena Kumari; Chandra Prakash Meena; Bhupender Singh; Pooja Sharma (Journal of Oilseed Brassica, 2026)
Water scarcity along with poor quality irrigation water is a major threat to mustard production in Western Rajasthan. Thepresent study was conducted to assess the effect of a plant growth regulator (PGR) i.e., brassinosteroid on the performanceof Indian mustard during the 2018-19 to 2019-20. A field experiment was conducted with two treatments i.e., a control(without PGR) and two foliar sprays of PGR-brassinosteroid (2 ppm) at 30 and 60 days after sowing and replicated at tenfarmer’s fields. The finding revealed that the mustard yield was significantly reported higher with PGR-brassinosteroidas compared to the control. The nutrient use efficiency and water productivity were significantly enhanced with PGRbrassinosteroidover the control. The net returns per unit of investment was recorded 3.21 with PGR-brassinosteroidwhich was significantly superior over the control. Thus, it can be concluded that the application of PGR-brassinosteroidmay be one of the good options to sustain the productivity of mustard under water stress condition of WesternRajasthan.